Emotional intelligence and social skills of children with special educational needs: diagnostic-research aspect - Duchyminska, Tamara; Kots, Mykhailo; Kulchytska, Anna (Psychological Prospects Journal, 2022)
Purpose. The article is devoted to the research of the peculiarities in the manifestation of social skills and the development level of emotional intelligence in aspect of children with special educational needs. Theoretical analysis and systematization of scientific sources allowed us to state the following: the emotional sphere and the emotional intelligence of children with special needs have their own characteristics - reduced ability to regulate behavior arbitrarily, increased excitability, or conversely inhibition; the structure of emotional intelligence includes self-awareness, self-control, motivation and social skills; social skills are a set of landmarks and formed actions that allow a child to socialize successfully (expression of feelings and emotions, skills of interpersonal interaction, situational regulation of emotions, etc.). Methods. The empirical part of the study was based on methods lsid: "Diagnosis of emotional intelligence" by N. Hall; D. Lusin’s "EmIn Questionnaire" and A. Holstein’s "Social Skills Questionnaire". Results. As a result of the research in the field of the development of emotional intelligence and social skills of children with special educational needs was established the following. The integrative indicator of the emotional intelligence of children with special educational needs has a mostly low level of formation. The subjects have a low level of emotions self-control and awareness of them. Indicators of intrapersonal emotional intelligence show that the majority of subjects has the average level of development, characterized by understanding of their own emotions and the ability to manage them. Respondents have certain abilities to control the expression, the ability to control the external manifestations of their emotions. Research on interpersonal emotional intelligence has allowed to state that level of development in this field is low. Subjects have difficulty in understanding other people’s feelings and intentions. The study of social skills of respondents showed a high level of development of this indicator, which is characterized by initial skills, skills of reaction to the opinion of another person, skills of planning future actions, skills of alternatives to aggressive behavior. At the same time, subjects have low level of development of self-expression skills. Conclusions. The study provided an opportunity to identify features of emotional intelligence and social skills in children with special educational needs. Prospects for further research are to study the dynamics of changes in the structural components of emotional intelligence and to develop psycho-correctional programs aimed to increase the emotional intelligence and social skills level.